PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK, TALK, WRITE TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IX SMP NEGERI 7 PADANG - Rafelina, Tisya Putri (Departemen Matematika, 2024)
Learning outcomes are a metric used to determine how well students have acquired the subject matter taught by the teacher. In fact, the mathematics learning outcomes for class IX students at SMP Negeri 7 Padang remain relatively poor. Low learning results can be caused by passive learning and ineffective learning methods. The approach offered is the Think Talk Write (TTW) cooperative model. The research methodology employed is descriptive and quasi-research, with a Nonequivalent Posttest-Only Control Group Design. The t-test analysis of the learning outcomes test provides a P-value of 0.000 with a significance level of α = 0.05. The data analysis results revealed that the TTW type cooperative learning model produces better learning outcomes than direct learning, and students' mathematics learning outcomes improve as a result of the quiz scores acquired while utilizing the TTW type cooperative learning model.Keywords– Think Talk Write, Learning outcomes, Direct Learning